Nuclear morphometric analysis in gastrointestinal stromal tumors: A preliminary study - Şükrü Oğuz ÖZDAMAR; Sibel BEKTAŞ; Sevim ERDEM ÖZDAMAR; Gökhan GEDİKOĞLU and Banu DOĞAN GÜN and Burak BAHADIR (Turkish Journal of Gastroenterology, 2019)
-